PERENCANAAN PREVENTIVE MAINTENANCE LINE PRODUKSI DENGAN METODE RCM (RELIABILITY CENTERED MAINTENANCE) DI PT RAYA - Dhany Ar-Royyan; M. Nushron Ali Mukhtar (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2023)
Maintenance on the machine is an activity that is needed to keep the system or equipment always in good condition when it will be used. The purpose of maintenance is to keep every component on the machine well maintained and can minimize costs or losses incurred due to long downtime. The RCM (Reliability Centered Maintenance) method is a method used to determine the planning of maintenance time intervals that lead to the ability of a machine to operate according to its function. The results of the FMEA analysis carried out, there are 3 machine components in the production line, namely forming paper with an RPN value of 84.588, curling with an RPN value of 83.6, flanging with an RPN value of 80.496. The results of calculations through exponential distribution for maintenance time intervals on the 3 components are Forming Paper of 0.407 hours, Curling of 0.457 hours, Flanging of 0.435 hours. the results of the reliability of the three components are Forming Paper of 1.42, Curling of 5.21, Flanging of 4.98.Â  Based on the risk analysis carried out on the possibility of risk, the results show that the level of risk on 3 components is at a medium or medium risk level. The maintenance method used is visual check and preventive maintenance planning.